Ergonutrition Supplementation and Recovery in Water Polo: A Systematic Review - Miguel Ortega, Álvaro; Barrenetxea Garcia, Josu; Rodríguez Rodrigo, María Azucena; García Ordóñez, Enrique; Mielgo Ayuso, Juan; Calleja González, Julio (MDPI, 2025)
Background: Water polo (WP) is a high-intensity team sport that requires a combi nation of physical endurance, muscular strength, speed, and specific technical skills. Due to the demanding and prolonged nature of this sport, adequate and balanced nutrition plays a fundamental role in athletes¿ performance, recovery, and overall health maintenance. Ob jectives: We aimed to compile all available information on the importance of ergonutrition and supplementation in the recovery of WP players. This will help in understanding this sport¿s specific challenges and requirements, enabling players and coaches to design more effective recovery plans to optimize performance, achieve goals, and successfully cope with intense training and competition. Method: English-language publications were searched in databases such as Web of Science, Scopus, SciELO Citation Index, Medline (PubMed), KCI Korean Journal Database, and Current Contents Connect using a series of keywords such as WP, nutrition, recovery, and ergogenic aids individually or in combination. Results: In the field of ergonutritional recovery in WP, certain supplements such as whey protein, beta-alanine, L-arginine, spirulina, and copper can be beneficial for improving performance and recovery. In some cases, WP athletes may consider using ergogenic supplements to further improve their performance and recovery process. However, it is important to bear in mind that any supplement should be carefully evaluated under the supervision of a health professional or a sports nutritionist, as some supplements may present side effects or unwanted interactions. Conclusions: Adequate ergogenic nutrition adapted to the needs of WP players is essential not only to optimize their athletic performance but also to ensure effective recovery and maintain their long-term health and general well-being. The application of these strategies should be evidence-based and tailored to the individual needs of the players and the specific demands of the sport. Future experimental research that can confirm our results is essential. Keywords: water polo; nutrition; recovery; performance; ergogenic aids
Keywords: water polo; nutrition; recovery; performance; ergogenic aids